The Continuation of Christ’s Mission by Religious: A Condition for the Renewal of Religious Life - Szewczul, Bożena (Prawo Kanoniczne, 2025)
The mission of Christ, which religious are called to continue through their consecrated life to God, has in recent decades lost its prominence within religious communities. The widespread identification of mission with the evangelization of nations that do not know Christ —that is, with the missio ad gentes— and the frequent use of the term to describe the role of a formator or the development plans of universities, businesses, or institutions has blurred the meaning of Christ's saving mission, reducing it to professional activity, employment, or the apostolic works managed by religious institutes. The misunderstandings that have arisen around these concepts have, to a great extent, estranged religious life from its core identity. Moreover, the awareness among contemporary religious of their obligation to embody and continue Christ’s mission through their lives is steadily diminishing. It can be argued that the crisis of religious life lies not so much in the decline in the number of religious, but in a lack of spiritual fidelity to its essential mission. It seems that deepening the awareness of religious regarding the essence of their participation in Christ's mission could restore a deeper sense of meaning and contribute to its long-awaited renewal.